Programa tutorial para mejorar la orientación vocacional en estudiantes de quinto grado de secundaria de la Institución Educativa José Olaya Balandra, Iquitos 2023 - De la Cruz Perez, Giordania Nelida (2024)
The present research aimed to evaluate the effectiveness of the tutorial program in improving the vocational guidance of fifth-year high school students at the José Olaya Balandra educational institution, located in Iquitos, during the year 2023. The study adopted a manipulative approach with a quasi-experimental design. It included a population of 128 students, of which a sample of 65 was formed, distributed in two groups: one manipulative of 34 students and another support of 31 students. Both groups were given a pre- and post-program test. For data collection, a questionnaire on vocational guidance was used, which was approved by an expert judgment, where a score of 82.3% and a reliability of 0.86 (86%) were obtained, which guaranteed its relevance and applicability. The descriptive statistical analysis shows that, after the implementation of the tutorial program, the experimental group obtained 67.6% (23 students) at the good level of vocational guidance, 17.6% (6 students) at the average level, and 14.7% (5 students) at the poor level. These data were contrasted through the Wilcoxon hypothesis test for related samples, obtaining a p-value of 0.000, which is less than 0.05. These results confirmed that the tutorial program had a significant impact on the improvement of vocational guidance.